Interest-bearing Debt and Islamic Debt vs. Shariah-compliant firms’ Performance Empirical Evidence from Malaysia - Osman Sayid Hassan Musse; Abdullah Mohammed Ahmed Ayedh; Fauzias Mat Nor (PSYCHOLOGY AND EDUCATION, 2024)
Indexed by ERA